Historically Black Colleges and Universities Are Vital and Valuable to the United States - Koch, James; Swinton, Omari (International Higher Education, 2023)
Though Historically Black Colleges and Universities (HBCUs) are little recognized, both in the United States and internationally, rigorous empirical analysis reveals that given their circumstances, they typically perform at a high level. This is the first comprehensive empirical analysis that has examined the performance of HBCUs.